2016
DOI: 10.1002/1873-3468.12324
|View full text |Cite
|
Sign up to set email alerts
|

A single mutation converts bacterial Na+‐transporting rhodopsin into an H+ transporter

Abstract: Na(+) -rhodopsins are light-driven pumps used by marine bacteria to extrude Na(+) ions from the cytoplasm. We show here that replacement of Gln123 on the cytoplasmic side of the ion-conductance channel with aspartate or glutamate confers H(+) transport activity to the Na(+) -rhodopsin from Dokdonia sp. PRO95. The Q123E variant could transport H(+) out of Escherichia coli cells in a medium containing 100 mm Na(+) and SCN(-) as the penetrating anion. The rates of the photocycle steps of this variant were only ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…In reality, KR2 pumps sodium ion exclusively under physiological conditions in which the concentration of the sodium ion is much greater than that of protons. The fact that Q123D/E only pumps protons is consistent with the competitive uptake model, 83 where Q123 contributes to efficient sodium uptake (Figure 5B, left). 64,95 A comparison of the permeability of channels, transporters, and flagella motor complexes to sodium ions and protons has been reported.…”
Section: Photocycle Dynamics Of Light-driven Sodium-pumping Rhodopsinssupporting
confidence: 82%
“…In reality, KR2 pumps sodium ion exclusively under physiological conditions in which the concentration of the sodium ion is much greater than that of protons. The fact that Q123D/E only pumps protons is consistent with the competitive uptake model, 83 where Q123 contributes to efficient sodium uptake (Figure 5B, left). 64,95 A comparison of the permeability of channels, transporters, and flagella motor complexes to sodium ions and protons has been reported.…”
Section: Photocycle Dynamics Of Light-driven Sodium-pumping Rhodopsinssupporting
confidence: 82%
“…oxidase [28,29], and Na + -proteorhodopsins [59,60]. Consistent with the above explanation for the effect of HQNO, we showed that in the presence of HQNO, the Na + /H + antiporter monensin (dissipating transmembrane [Na + ] and [H + ] gradients) abolished the HQNO-induced stimulation of the motility rate (Figure 6c).…”
Section: Resultssupporting
confidence: 87%
“…As a result, the activity of the primary Na + pump increases, followed by an increase in ∆pNa with the simultaneous dissipation of the electric potential on the membrane. The stimulation effect of protonophore uncouplers on Na + pumping has been described for a number of ∆s-generating proteins [52], among which are Na + -pumping NADH-quinone oxidoreductases [53], Na + -ATPases [54][55][56][57][58], recently described Na + -pumping cytochrome oxidase [28,29], and Na + -proteorhodopsins [59,60]. Consistent with the above explanation for the effect of HQNO, we showed that in the presence of HQNO, the Na + /H + antiporter monensin (dissipating transmembrane [Na + ] and [H + ] gradients) abolished the HQNO-induced stimulation of the motility rate (Figure 6c).…”
Section: Resultsmentioning
confidence: 99%
“…10 Understanding the key residues involving in the ions transports in microbial rhodopsins permits the possibility to manipulate the pumping activities. 38,39 Site directed mutagenesis was applied to convert pumping activity. By converting the proton accepter in BR, D85T pumps Clinwardly similar to HR.…”
Section: Retinal Proteinsmentioning
confidence: 99%
“…The advantage of cells hyperpolarization using sodium ion instead of proton is the capability to manipulate the cell membrane potential without affecting pH of the cells. 170,171 After the discovery, numerous studies based on time-resolved visible 2,48 , FTIR 3,52,54,172 , Raman 4 , NMR spectroscopies 5,173 , X-ray crystallography 16,17,50 , and site directed mutagenesis 1,16,17,38,40 have been performed to elucidate the molecular mechanism and ion transport pathway of the protein. Crystal structures of the wild type and important mutants in the dark state 16,17,50 have been reported on the PDB database.…”
Section: Transport Assaymentioning
confidence: 99%